Pengaruh Kepemimpinan Kepala Madrasah, Disiplin dan Motivasi Kerja terhadap Kinerja Guru Matematika MTs Negeri Se-Kabupaten Tanah Datar - Mira, Rossi; Adripen, Adripen; Afriyani, Dona (STKIP PGRI SITUBONDO, 2024)
Teacher performance is a learning process as an effort to develop existing activities into better activities so that teacher goals have been achieved well through a learning activity carried out by the teacher by the targets and objectives. The method used in this study is the correlational quantitative research method. This correlational quantitative research method aims to explain a phenomenon by utilizing numbers that describe the characteristics of the subject under study. This research was conducted in MTs Negeri throughout Tanah Datar Regency. The population in the study was MTs mathematics teachers in Tanah Datar Regency as many as 100 people—sampling technique simple random sampling technique or simple random sample, for data analysis techniques use the Normality Test, Homogeneity Test, Linearity Test, Multicollinearity Test, Autocorrelation Test, Heterokedacity Test, Simple Linear Regression, and Multiple Linear Regression. Based on the results of research and discussion, it can be concluded that there is a significant influence between the leadership of the head of the madrasah and the performance of mathematics teachers of MTs Negeri Se-Kabupaten Tanah Datar. There is a significant influence between work disciplines on the performance of MTs State mathematics teachers in Tanah Datar District. There is a significant influence between work motivation and the performance of MTs Negeri mathematics teachers in Tanah Datar District. There is a significant influence between the leadership of the head of the madrasah, discipline, and motivation of teacher work on the performance of mathematics teachers MTs Negeri Se-Kabupaten Tanah Datar.